Non-monotonic temporal variation in fearlessness about death: A latent class growth analysis. (October 2018) - Zuromski, Kelly L.; Cero, Ian; Witte, Tracy K.
Highlights: Fearlessness about death is proposed to increase or remain stable over time. Tested this hypothesis using latent class growth modeling. Three distinct FAD classes emerged, including a Low/Decreasing fearlessness class. This class contradicts prior research and suggests fearlessness can fluctuate downward. Findings highlight need to better test theoretical assumptions related to capability for suicide. Abstract: According to the Interpersonal-Psychological Theory of Suicide, fearlessness about death is proposed to increase monotonically (i.e., either increasing or remaining stable) and thus, not be amenable to intervention; however, this assumption has not been explicitly tested. We utilized latent class growth modeling to examine the trajectory of this construct over a brief interval (i.e., data collected every three days over a 15-day time period) among college students ( N = 716), and found evidence that fearlessness does not monotonically increase. Specifically, our analyses revealed three classes, each with distinct trajectories over time: a High/Increasing class (i.e., high intercept, significantly increasing slope), Average/Stable class (i.e., average intercept, flat and non-significant slope), and Low/Decreasing class (i.e., low intercept, significantly decreasing slope). The emergence of a Low/Decreasing group is in contrast to the assertion that fearlessness cannot decrease over time. Exploratory results also indicated that lifetime exposure to certain events (e.g., abuse, injury) was associated with membership in the Low/Decreasing class, suggesting that some individuals may be responding differently to painful and/or fear-inducing stimuli than the IPTS predicts. Our findings contradict the current conceptualization of fearlessness about death, and suggest instead that this construct fluctuates upward and downward over a brief interval.